Which kind of feedback has a greater impact on individuals with social anxiety: facial or textual? An ERP study. Issue 4 (18th January 2021) - Yu, Xianglian; Lin, Wuji; Kong, Xiangtian; Chen, Danwen; Zheng, Minxiao; Wei, Qiang; Gao, Chao
Abstract : The present study is the first to compare the examined electrophysiological activity of facial and textual feedback of students with social anxiety after they finished a visual search task. Compared to textual feedback, facial feedback is much more effective. Specifically speaking, positive facial feedback caused stronger feedback-related negativity (FRN), and negative facial feedback caused late positive potential (LPP) of stronger amplitude. These changes in the FRN component (associated with feedback) and LPP (related to controlled attention engagement) provide clues about the interplay between anxiety and attention allocation in processing facial feedback. The results have implications for identifying the feedback format that will be most helpful for individuals with social anxiety.